Benefits and geography of international collaboration for PhD students in biology from four global south countries - Mahdjoub, Hayat; Baaloudj, Afef; Chaib, Sara; Ramírez-Castañeda, Valeria; Contreras, Leidy Alejandra Barragan; González-Tokman, Daniel; Villada-Bedoya, Sebastián; Rocha-Ortega, Maya; Córdoba-Aguilar, Alex; Khelifa, Rassim (Frontiers in Education, 2023)
Collaboration is a fundamental aspect of scientific research and innovation. Fair collaborations between scientists from different identities or positions of power (e.g., Global North and Global South scientists) could have a great impact on scientific knowledge and exchange. However, there are existing limitations to the potential of Global South scientists to collaborate fairly. Here we assess the impact and geographic distribution of international collaborations for PhD students in biological sciences in four Global South countries (two from Africa: Algeria and Morocco, and two from the Americas: Colombia and Mexico), where students typically have low English proficiency. We show that overall international collaboration, particularly with the Global North, increased the probability of publishing in a journal with an impact factor and achieved more citations. Most international collaborators were affiliated with French-speaking countries for Algerian and Moroccan students and Spanish and English-speaking countries for Colombian and Mexican universities, suggesting that language and geopolitical history might play a role in shaping the selection of international collaborators. While the results highlight the benefit of international collaboration for researchers in the Global South, we discuss that the current metrics of scientific success could maintain the dependence of Global South scientists on the Global North.